Study of The Effect of Heating During Fabrication On The Insulation Resistance of The 75 Mw Generator Stator at the Malea Energy Stage-2 BMS PLTA - Rompon, Aldy; Suhardi, Iwan (Teknik Elektro, Universitas Negeri Makassar, 2025)
This study aims to assess the impact of heating during fabrication on the insulation resistance of the 75 MW generator stator at the Malea Energy Stage-2 BMS hydroelectric power plant. Using a quantitative descriptive method and documentation for data collection, researchers analyzed secondary data archived by staff at the plant. The results showed a significant increase in insulation resistance from 6,930 MΩ at 39°C to 16,300 MΩ at 80°C. The Arrhenius equation revealed an activation energy of 19,083.41 J/mol, indicating good thermal resistance. A linear regression analysis showed a strong positive relationship between temperature and insulation resistance, with a correlation coefficient (R) of 0.9915 and an R^2 value of 0.9831. The heating process met the Toshiba SF80.35-12/5200 standard and the National Standard of the People’s Republic of China, proving effective in reducing humidity, accelerating resin hardening, and improving insulation durability.